Pengaruh Minat terhadap Perilaku Hedonisme - Adi Noviansyah; Riyanto (Bandung Conference Series: Communication Management, 2023)
Abstract. The growth of technology has had a major impact on human life and civilization, for example, the emergence of social media due to the rapid development of technology. Technology in the current era of globalization provides many benefits that have an impact on social aspect, making interaction easy and fast. Especially new media, in the form of the internet with various applications such as web, email, blogspot, web social network, online games, online books, online newspapers, web, various videos and their diversity. In the development of social media such as TikTok, it has benefits that can be presented by its users, but has drawbacks that can change the perception of its user, especially young people who are consumers and make a hedonistic lifestyle among teenagers. With a qualitative research method, we tried to observe TikTok follower Medy Renaldy in relation to the use of social media and adolescent interest in reviewing toys that encourage hedonistic behavior. With a population of 96.100 followers and the Slovin method, a sample of 100 people was obtained. From the research, the regression equation Y=7,705 + 0,673 X, and R=0,815 and Rsquare = 0,664 or 66,4% which means that Medy Renaldy TikTok content has an influence of 66,4% on adolescent hedonism behavior, and the remaining 33,6% is influenced by other factors not discussed in this study. Abstrak. Pertumbuhan teknologi sangat berpengaruh besar terhadap kehidupan dan peradaban manusia, seperti, kemunculan media sosial akibat perkembangan teknologi yang begitu cepat. Teknologi pada masa globalisasi saat ini memberikan banyak manfaat yang berdampak pada aspek sosial, dalam berinteraksi menjadi mudah dan cepat. Terutama media baru, berupa internet dengan berbagai aplikasinya seperti web, email, blogspot, web social network, permainan online, buku online, koran online, web berbagai video dan keberagamannya. Dalam perkembangan media sosial seperti TikTok mempunyai manfaat yang dapat disajikan oleh penggunanya, namun memiliki kekurangan yang dapat mengubah persepsi penggunanya khususnya kaum muda yang bersifat consumer serta menjadikan gaya hidup hedonism dikalangan remaja. Dengan metode penelitian kuantitatif berusaha mengamati follower TikTok Medy Renaldy dalam kaitannya dengan penggunaan media sosial dan minat remaja dalam mereview mainan yang mendorong perilaku hedonism. Dengan populasi sebesar 96.100 followers dan metode Slovin diperoleh sampel sebanyak 100 orang. Dari penelitian diperoleh persamaan regresi Y= 7,705 + 0,673 X, dan R= 0,815 serta Rsquare = 0,664 atau 66,4% yang berarti bahwa konten TikTok Medy Renaldy memiliki pengaruh sebesar 66,4% terhadap perilaku hedonism remaja, dan sisanya sebesar 33,6% dipengaruhi oleh faktor lain yang tidak dibahas dalam penelitian ini.